If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(3x + -2) + -29 = 3x + 1 Reorder the terms: 3(-2 + 3x) + -29 = 3x + 1 (-2 * 3 + 3x * 3) + -29 = 3x + 1 (-6 + 9x) + -29 = 3x + 1 Reorder the terms: -6 + -29 + 9x = 3x + 1 Combine like terms: -6 + -29 = -35 -35 + 9x = 3x + 1 Reorder the terms: -35 + 9x = 1 + 3x Solving -35 + 9x = 1 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -35 + 9x + -3x = 1 + 3x + -3x Combine like terms: 9x + -3x = 6x -35 + 6x = 1 + 3x + -3x Combine like terms: 3x + -3x = 0 -35 + 6x = 1 + 0 -35 + 6x = 1 Add '35' to each side of the equation. -35 + 35 + 6x = 1 + 35 Combine like terms: -35 + 35 = 0 0 + 6x = 1 + 35 6x = 1 + 35 Combine like terms: 1 + 35 = 36 6x = 36 Divide each side by '6'. x = 6 Simplifying x = 6
| 5a^2+13a=6 | | m^2+5m+7=0 | | 44-99x^2=0 | | 6x-(5x+8)=-4 | | 9n-3n+5= | | 6x-5x+8=-4 | | 5x+3=4(x-4) | | w^2=13w-40 | | 3r^2=-r | | 3n^2=32-4n | | y=-6x-3 | | 3(2y-7)=-2(y+1)-1 | | 32x^2-54x-5= | | -(p-8)-2(3p+5)=8-2p | | 5r^2=-8r | | 2x^2-15=-7+14x | | 3x-15=2x+10 | | 0.05h+0.4(0.8-h)=0.54+0.02h | | 16+3*5=3X | | 4r=3s | | 32x^2-32x+8=0 | | 2x-12=6x-4 | | x^2-0.6x=0.2 | | 0=-4x^2+8x-2 | | Y=-4x^2+8x-2 | | 2u+2=5u-10 | | x^2+13x+45=5 | | x=180+5x | | x^2-15x+44= | | -(b-4)+2.=6 | | 0=x^2+7x-2 | | 0.6t-2=-3 |